2018
DOI: 10.1111/are.13788
|View full text |Cite
|
Sign up to set email alerts
|

Osteological development and deformities in hatchery-reared longtooth grouper (Epinephelus bruneus ): Vertebral column, dorsal-fin supports and caudal-fin skeleton

Abstract: Skeletal deformities are one of the serious problems in hatchery-reared longtooth grouper (Epinephelus bruneus). In this study, seed production of longtooth grouper was carried out in four large hatchery-grade tanks. Osteological development of the vertebral column, caudal-fin skeleton and dorsal-fin supports in larvae and juveniles was described. The vertebral ontogeny started at 4.8 mm total length (TL) with the formation of neural spines 2 and 3, and the vertebral centra began forming at 5.3 mm TL. By 16 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…As for the Atlantic halibut Hippoglossus hippoglossus L., ossification of the vertebral centra came up cephalad and caudad from the posterior haemal region of the vertebral column where the ossification started originally (Lewis & Lall, 2006), which is similar to P. stellatus, except for its origin of ossification from the latter haemal region. As for the longtooth grouper Epinephelus bruneus Bloch, ossification of the vertebral centra was conducted by an anterior to posterior direction (Takashi et al, 2018).…”
Section: Vertebral Column Developmentmentioning
confidence: 99%
“…As for the Atlantic halibut Hippoglossus hippoglossus L., ossification of the vertebral centra came up cephalad and caudad from the posterior haemal region of the vertebral column where the ossification started originally (Lewis & Lall, 2006), which is similar to P. stellatus, except for its origin of ossification from the latter haemal region. As for the longtooth grouper Epinephelus bruneus Bloch, ossification of the vertebral centra was conducted by an anterior to posterior direction (Takashi et al, 2018).…”
Section: Vertebral Column Developmentmentioning
confidence: 99%
“…In recent decades, fishery biologists have become more interested in skeletal deformity diseases of wild and reared fish (Kužir et al, 2015). Many types of deformities (Afonso et al, 2000;Sato, 2006;Jawad et al, 2017;Jawad & Ibrahim, 2018) have been reported from the variety of fish species living in the different habitats (Iwasaki et al, 2018). It was reported that these deformities affect mostly the ribs, fins, cranium and vertebral column of fish (De La Cruz-Aguero & Perezgomez-Alvarez, 2001).…”
Section: Introductionmentioning
confidence: 99%